2008
DOI: 10.1152/ajpregu.00666.2007
|View full text |Cite
|
Sign up to set email alerts
|

Reduced volume but increased training intensity elevates muscle Na+-K+ pump α1-subunit and NHE1 expression as well as short-term work capacity in humans

Abstract: Iaia FM, Thomassen M, Kolding H, Gunnarsson T, Wendell J, Rostgaard T, Nordsborg N, Krustrup P, Nybo L, Hellsten Y, Bangsbo J. Reduced volume but increased training intensity elevates muscle Na ϩ -K ϩ pump ␣1-subunit and NHE1 expression as well as short-term work capacity in humans.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

25
151
4
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 105 publications
(192 citation statements)
references
References 35 publications
25
151
4
3
Order By: Relevance
“…In contrast, other studies implementing intense intermittent training have observed elevated levels of the Na ϩ -K ϩ pump subunits (3,18,34). In the study by Nielsen et al (34) untrained subjects had a higher content of the Na ϩ -K ϩ pump subunits ␣ 1 , ␣ 2 , and ␤ 1 after 8 wk of intense one-legged knee-extensor exercise, and the Na ϩ -K ϩ pump ␣ 1 and ␣ 2 subunits have also been shown to be upregulated in trained runners after 4 -9 wk of intensified and reduced training (3,18). The difference between these studies and the present study may be related to exercise modalities.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…In contrast, other studies implementing intense intermittent training have observed elevated levels of the Na ϩ -K ϩ pump subunits (3,18,34). In the study by Nielsen et al (34) untrained subjects had a higher content of the Na ϩ -K ϩ pump subunits ␣ 1 , ␣ 2 , and ␤ 1 after 8 wk of intense one-legged knee-extensor exercise, and the Na ϩ -K ϩ pump ␣ 1 and ␣ 2 subunits have also been shown to be upregulated in trained runners after 4 -9 wk of intensified and reduced training (3,18). The difference between these studies and the present study may be related to exercise modalities.…”
Section: Discussionmentioning
confidence: 66%
“…Ϫ exchanger (NKCC1) may have played a role in the altered K ϩ handling since in a recent study the expression of NKCC1 was higher (ϳ15%) after 4 wk of speed endurance training in trained runners (18). In the present study we were unable to examine changes in cell surface expression of ion transporting proteins and cannot, as such, exclude the possibility that changes in K ϩ handling are in part due to alterations in the cell surface expression of K ϩ transporting proteins such as the Na ϩ -K ϩ pump subunits, NKCC1, Kir2.1 and Kir6.2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, athletes with faster recovery after brief intense exercise bouts are likely to perform better in intermittent sports. High-intensity interval training could be particularly well suited for improving intermittent endurance performance (Iaia et al 2008). As a result, it could be that a faster ultra short-term HRR reflects a positive adaptation to highintensity intermittent endurance training and, therefore, represents a superior capacity in performance events (Bosquet et al 2008;Lamberts et al 2009a).…”
Section: Discussionmentioning
confidence: 99%